1994
DOI: 10.1128/aac.38.4.738
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo activities of sparfloxacin against Mycoplasma pneumoniae

Abstract: The in vitro and in vivo activities of sparfloxacin against Mycoplasma pneumoniae were compared with those of erythromycin, levofloxacin, ofloxacin, and minocycline. The MICs of sparfloxacin, erythromycin, levofloxacin, ofloxacin, and minocycline for 90%7o of the 43 M. pneumoniae strains tested were 0.063, 0.016, 0.5, 1, and 0.5 ,ug/ml, respectively. In the experimental pulmonary M. pneumoniae infection model in Syrian golden hamsters, sparfloxacin was as eflective as erythromycin when orally administered at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The expansion of 14-ML, azithromycin, and telithromycin usage for RTI worldwide may increase ML-resistant M. pneumoniae. Further evaluation for new quinolones, such as sparfloxacin (10) and sitafloxacin, will be necessary in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of 14-ML, azithromycin, and telithromycin usage for RTI worldwide may increase ML-resistant M. pneumoniae. Further evaluation for new quinolones, such as sparfloxacin (10) and sitafloxacin, will be necessary in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…MINO has been widely used for the treatment of various infections including those of the respiratory tract because it is active not only against common gram-positive and -negative microbes, but also against Mycoplasma, Chlamydia and Rickettsia [1][2][3]. It has been shown that MINO penetrates easily into the cell [4], but little is known of the ratio of penetration of MINO into lung tissue and sputum after intravenous infusion.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro antimycoplasmal susceptibility tests have not been standardized; one was performed in this study by the broth microdilution method, which has been recently applied for several potent antibiotics for treatment of M. pneumoniae infections (6,8,9,12,14,15). M. pneumoniae isolates were grown to a concentration of 10 8 CFU/ml in modified Chanock broth medium (3) consisting of 7 parts pleuropneumonia-like organism (PPLO) broth without crystal violet (Difco Laboratories, Detroit, Mich.), 2 parts uninactivated horse serum, and 1 part a mixture of 25% fresh yeast extract, 1% glucose, and 0.002% phenol red adjusted to a pH of 7.8 with 1 N sodium hydroxide.…”
mentioning
confidence: 99%
“…MIC 50 and MIC 90 were defined as the drug concentrations required to inhibit the growth of 50 and 90% of the total number of isolates tested, respectively (6,8,9,12,14,15). As a control for potential interactions between antibiotics, medium components, and pH, which could potentially affect the observed MICs, the American Type Culture Collection bacterial reference strain Staphylococcus aureus ATCC 29213 was inoculated into microtiter plates containing Chanock broth.…”
mentioning
confidence: 99%